1999
DOI: 10.1007/s004649901100
|View full text |Cite
|
Sign up to set email alerts
|

Conversion factors for laparoscopic splenectomy for immune thrombocytopenic purpura

Abstract: Densely adherent adjacent structures, technical errors, and cardiopulmonary instability may preclude successful completion of laparoscopic splenectomies. Thorough preoperative evaluation with an emphasis on the cardiopulmonary system may elicit a cohort of individuals with ITP who are unlikely to undergo laparoscopic splenectomy successfully. This cohort also may include individuals with preoperative platelet counts less than 35,000 mm(-3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 6 publications
2
35
0
5
Order By: Relevance
“…In a report by Brody et al [18], the platelet count was identified as an important predictor of conversion, and the suggested cutoff point was 35 Â 10 9 /L. Since then, however, several other authors have shown that laparoscopic completion is feasible [3,18]. In our series, the platelet count did not affect the conversion rate, but because the group of patients with a low platelet count is small, in no way it excludes the possibility that the platelet count may play a role as a conversion factor.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a report by Brody et al [18], the platelet count was identified as an important predictor of conversion, and the suggested cutoff point was 35 Â 10 9 /L. Since then, however, several other authors have shown that laparoscopic completion is feasible [3,18]. In our series, the platelet count did not affect the conversion rate, but because the group of patients with a low platelet count is small, in no way it excludes the possibility that the platelet count may play a role as a conversion factor.…”
Section: Discussionmentioning
confidence: 96%
“…In a report by Brody et al [18], the platelet count was identified as an important predictor of conversion, and the suggested cutoff point was 35 Â 10 9 /L. Since then, however, several other authors have shown that laparoscopic completion is feasible [3,18].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is Table VI. Treatment of complications requiring surgical intervention often described in the literature [5,9,10,11,14,15]. More importantly, complication-driven conversions were reduced significantly, from 0.6% in the 1 st period to 0.27% and 0.26%.…”
Section: Discussionmentioning
confidence: 96%
“…In the next stage, the number of procedures performed laparoscopically increases significantly and the spectrum of indications broadens. Year after year, the rate of technically advanced procedures, such as Nissen fundoplication, cardiomyotomy, splenectomy and adrenalectomy, increases [8][9][10][11]. In spite of proven experience, the complexity of new procedures and freer qualification of patients prevent the total number of adverse events from falling substantially [8,10].…”
Section: Discussionmentioning
confidence: 99%
“…What is more, the size of the operated organ (both adrenal gland tumour and spleen) did not seem to considerably infl uence the means of fi nishing the operation. Connection between the conversion and the adrenal gland tumour (especially the pheochromocytoma type) during adrenalectomy, or the level of platelets in patients undergoing splenectomy was not observed (4,18,19,20).…”
Section: Discussionmentioning
confidence: 99%